Linking top and subsoil types, alteration and degassing processes at Rotokawa geothermal field, New Zealand - Montanaro, Cristian; Ray, Lena; Cronin, Shane J.; Calibugan, Aimee; Rott, Stefanie; Bardsley, Candice; Scheu, Bettina (Frontiers in Earth Science, 2023)
Surface geothermal expressions such as mud pools, fumaroles, mineral deposits, collapse pits, and hydrothermal eruption craters vary in scale and type over space and time. The evolution in space and time of these surficial thermal features strongly relates to alteration processes caused by hydrothermal fluids. The changes in the physical and mechanical properties of top and subsoils that can control fluid flow, degassing patterns, and occurrence of geothermal hazards remain understudied. The thermal area located south of the Rotokawa geothermal field (New Zealand) includes a variety of major natural surface thermal features and widespread sulphur deposits precipitated by acid–sulphate fluids in steam-heated zones. Decades of sulphur mining induced the formation of new thermal features. Such a setting represents an exemplary case study for investigating old and recently formed thermal features, soil characteristics, types and patterns of superposed hydrothermal alteration, and degassing processes. We combined field and laboratory methods to define groups of thermal features, soil types, and associated alteration. Their spatial distribution indicates that fluid circulation, alteration intensity, and degassing are strongly influenced by the local and regional geological and structural settings, as well as by mining activity. We found that at the water table level and within excavated areas, acidic fluids led to the deposition of mud deposits, sinters, and stromatolites around warm springs and mud pools. In the vadose, steam-heated portions, fluids generally leach and degrade the Taupo Pumice, resulting in broad unstable grounds and collapse structures, while extensive sulphur-encrusted grounds and sulphur-rich soils formed in excavated sites. In this framework, the degassing and fluid circulation within the top and subsoils are strongly affected by the dominant soil layer type, and in turn by its granulometry, texture, and alteration state. Our study of top and subsoils yields precious insights into surface expression variability, fluid–rock interaction processes, and sulphur deposition patterns within steam-heated zones. Processes at such a scale may strongly influence the migration of thermal manifestations, gas outputs, and ground subsidence within geothermal environments. From a broader perspective, our results will help assess the evolution of geothermal activity and related hazards in similar areas worldwide.